Pemahaman dan Kepedulian Penerapan Green Accounting: Studi Kasus UKM Tahu Tempe di Kota Bandar Lampung - Destia Pentiana (Jurnal Ilmiah ESAI, 2019)
The general objective of this study is to find out whether: 1) the SMEs of tofu and tempe in Bandar Lampung city have knowledge of the concept of green accounting 2) the SMEs of tofu and tempe in Bandar Lampung city care about the environment. The type of data used in this study is primary data, namely by interviewing and distributing questionnaires to the businessmen of tofu and tempe in Bandar Lampung city. Based on the results of the questionnaire, it was found that the understanding of the perpetrators of SMEs of tofu and tempe in Bandar Lampung city is still low because the preference of the interests of the actors of SMEs of tofu and tempe is still focused on operating profits not on product quality and environmental quality. The lack of awareness of environmental impacts that can affect the sustainability of its business is a factor that causes the low level of understanding. In terms of knowledge of the environmental costs, SMEs is also identified low. This is because the business actors are unable to identify what constitutes the components of environmental costs which also become a factor that causes low understanding of the SMEs. Keywords: Green Accounting, Environmental Costs, SMEs.